If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 10 = 4(x + -2) Reorder the terms: 10 + 5x = 4(x + -2) Reorder the terms: 10 + 5x = 4(-2 + x) 10 + 5x = (-2 * 4 + x * 4) 10 + 5x = (-8 + 4x) Solving 10 + 5x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 10 + 5x + -4x = -8 + 4x + -4x Combine like terms: 5x + -4x = 1x 10 + 1x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 10 + 1x = -8 + 0 10 + 1x = -8 Add '-10' to each side of the equation. 10 + -10 + 1x = -8 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = -8 + -10 1x = -8 + -10 Combine like terms: -8 + -10 = -18 1x = -18 Divide each side by '1'. x = -18 Simplifying x = -18
| t^2+6t-20=0 | | 3[4(4+1)]= | | -20-6r=-4(2r+3) | | t^2+6-20=0 | | 3[f(4)(4)+1]= | | -x-29=11+4x | | 3x=5(16) | | f(x)=0x^0 | | 3x*x=147 | | 14-2+11+3= | | 5x+15=8x+2 | | 2(d+3)=28 | | f(x)=2x^1+0x^0 | | 15+5z=-10 | | -24-4x=15-x | | 3(m+1)=13 | | f/x | | 2[x-3(0)]= | | 3(5x-2)=4(2x+6) | | 10(c+7)=90 | | -8y+9=13 | | -7(2f+8)=-126 | | f(x)=3x^2+2x^1+0x^0 | | X=(20-2x)*(40-2x) | | 14n+2=72 | | 10(s-5)=-98 | | x=(20-2x)(40-2x) | | f(x)=2senx | | x^4+x^3-8x^2+16x+6=0 | | 225=x^2-16x+68 | | 0=y^2-4y-1 | | 3(3s+6)=72 |